Foreign Bodies in Lower Airway in Children: Brief Review and Clinical Experience - Stoyan Markov; Petya Markova; Ivanka Karavelikova; Hristina Halacheva (Children)
Background: Foreign body aspiration is a preventable occurrence that carries a high risk of mortality in the pediatric population. Clinically, foreign body aspiration manifests as cough, followed by choking, which might not be given any consideration by the caregivers of the child. An episode of sudden wheezing can also raise the suspicion of a foreign body in the lower respiratory tract. The clinical findings depend on the type, size, and localization of the foreign body and include persistent cough, localized airway resistance, localized or diffuse wheezing, and difficulty breathing. A bronchoscopy is the procedure of choice for the removal of foreign bodies. Flexible bronchoscopy is increasingly being used as the initial diagnostic procedure in children with an uncertain history of choking, in the absence of physical and radiological lung changes, and in chronic complaints requiring the exclusion of a foreign body in the airways. Thus, the aim of this study was to describe our clinical experience with lower respiratory tract foreign body extraction in children over a period of five years. Materials and Methods: Over a 5-year period, 154 patients under the age of 18 underwent a bronchoscopy due to a suspected foreign body in the lower respiratory tract. Of these patients, 92% had an incident leading to acute respiratory distress, and 8% had no definite data on such an event in the anamnesis. Results: A foreign body in the respiratory tract was found in and extracted from 50 patients, and foreign bodies were absent in 104 of the cases. Conclusions: If a foreign body enters the lower respiratory tract, immediate and adequate actions are required to solve the problem. A bronchoscopy should be conducted in every suspected case of foreign body aspiration.